Time Management Skills That Work - Greshes, Warren (Ascent Audio, 2011)
Time management is the single most important skill you can master when it comes to your life, career or business! In this 30 minute session, Warren Greshes teaches you how to effectively manage your time, while taking you through a time test to determine what progress you have made so far. Learn how to prepare for and plan tasks according to priority and save extra time each day. Whether you're a salesperson with a large territory or you simply want to do things more efficiently, Time Management Skills That Work will show you how.